Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1162/089976602320263999
|View full text |Cite
|
Sign up to set email alerts
|

Center-Crossing Recurrent Neural Networks for the Evolution of Rhythmic Behavior

Abstract: A center-crossing recurrent neural network is one in which the null-(hyper)surfaces of each neuron intersect at their exact centers of symmetry, ensuring that each neuron's activation function is centered over the range of net inputs that it receives. We demonstrate that relative to a random initial population, seeding the initial population of an evolutionary search with center-crossing networks significantly improves both the frequency and the speed with which high-fitness oscillatory circuits evolve on a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…Large initial values would have probably resulted in networks where most neurons were saturated either fully on or off. A more general way to avoid this problem is given by Mathayomchan and Beer (2002).…”
Section: Appendix 1: Details Of the Genetic Algorithmmentioning
confidence: 99%
“…Large initial values would have probably resulted in networks where most neurons were saturated either fully on or off. A more general way to avoid this problem is given by Mathayomchan and Beer (2002).…”
Section: Appendix 1: Details Of the Genetic Algorithmmentioning
confidence: 99%
“…In this so-called "centre crossing configuration" all nodes in a CTRNN interact at the centre of their sigmoid transfer functions (Mathayomchan and Beer, 2002), a mathematical property that bears close resemblance to the biological ideas highlighted by Turrigiano, amongst others. Williams also demonstrated that signal propagation was improved within such centre crossing networks.…”
Section: Signal Propagationmentioning
confidence: 81%
“…One possible reason for these results can be induced from the original work on centre crossing CTRNNs (Mathayomchan and Beer, 2002). Here, it was demonstrated that the generation of rhythmic patterns evolved more readily in such networks.…”
Section: Signal Propagationmentioning
confidence: 91%
“…Many alternatives are available in the choice of the type of the kind of oscillator/neurons employed for the realization of the CPG, for instance sinusoidal [5], Hopf or adaptive frequency Hopf oscillator [6], Rayleigh [7], Van Der Pol [18], FitzHugh-Nagumo [3], Hopfield [19], Hopfield with synaptic depression [20] or Matsuoka's [21].…”
Section: Cpg Networkmentioning
confidence: 99%